Phraseological Units with the Component “Heart” Expressing Love and Devotion - Ghazaryan, Hasmik (Armenian Folia Anglistika, 2010)
The present article aims to study, analyze and compare phraseological units with the component “heart” expressing love and devotion in Armenian, Russian and English. These phraseological units in the languages mentioned have structural, grammatical, stylistic, as well as semantic similarities and differences. The similarities reflect the peculiarities of the linguistic thinking of the language bearers, whereas the differences witness the peculiarities of the mentality of the given nation.